Conversion of acetylcholinesterase to butyrylcholinesterase: modeling and mutagenesis. - Harel, M (1992)
Torpedo acetylcholinesterase (AcChoEase, EC 3.1.1.7) and human butyrylcholinesterase (BtChoEase, EC 3.1.1.8), while clearly differing in substrate specificity and sensitivity to inhibitors, possess 53% sequence homology; this permitted modeling human BtChoEase on the basis of the three-dimensional structure of Torpedo AcChoEase. The modeled BtChoEase structure closely resembled that of AcChoEase in overall features. However, six conserved aromatic residues that line the active-site gorge, which is a prominent feature of the AcChoEase structure, are absent in BtChoEase. Modeling showed that two such residues, Phe-288 and Phe-290, replaced by leucine and valine, respectively, in BtChoEase, may prevent entrance of butyrylcholine into the acyl-binding pocket. Their mutation to leucine and valine in AcChoEase, by site-directed mutagenesis, produced a double mutant that hydrolyzed butyrylthiocholine almost as well as acetylthiocholine. The mutated enzyme was also inhibited well by the bulky, BtChoEase-selective organophosphate inhibitor (tetraisopropylpyrophosphoramide, iso-OMPA). Trp-279, at the entrance of the active-site gorge in AcChoEase, is absent in BtChoEase. Modeling designated it as part of the "peripheral" anionic site, which is lacking in BtChoEase. The mutant W279A displayed strongly reduced inhibition by the peripheral site-specific ligand propidium relative to wild-type Torpedo AcChoEase, whereas inhibition by the catalytic-site inhibitor edrophonium was unaffected.